Faculty Senate, Minutes, November 15, 2001 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2001)
Valdosta State University. Faculty Senate, Minutes, November 15, 2001. Chairman, President H.C.Bailey; Vice Chairman Executive, Vice President L.Levy; Secretary, Dr. R. Hull; Parliamentarian, Dr. D. Boyd;
1 electronic record. Valdosta State University. Faculty Senate, Minutes, November 15, 2001. 3 pages.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records